Evidence and information: the challenges for Medicine in the next decade (Perspectivas em Ciência da Informação, 2009)
This document addresses the information explosion and the advances in medicine that contributed with Evidence-Based Medicine (EBM), which is changing medical practice towards the constant use of current scientific evidence in the clinical decision making. EBM also can expand the information professional’s role beyond the information search, allowing his involvement in the selection and critical appraisal of literature, according the clinical librarianship model, where the librarian is considered an integral part of multidisciplinary health teams.